A non‐parametric double homogeneously weighted moving average control chart under sign statistic. (7th December 2020) - Riaz, Muhammad; Abid, Muhammad; Shabbir, Aroosa; Nazir, Hafiz Zafar; Abbas, Zameer; Abbasi, Saddam Akber
Abstract: In practical situations, the underlying process distribution sometimes deviates from normality and their distribution is partially or completely unknown. In that instance, rather than staying with/depending on the conventional parametric control charts, we consider non‐parametric control charts due to their exceptional performance. In this paper, a new non‐parametric double homogeneously weighted moving average sign control chart is proposed with the least assumptions. This chart is based on a sign test statistic for catching the smaller deviations in the process location. Run‐length (RL) properties of the proposed chart are studied with the help of Monte Carlo simulations. Both in‐control and out‐of‐control RL properties show that the proposed chart is a better contender as compared to some existing charts from the literature. A real‐life application for practical consideration of the proposed chart is also provided.